College Graduates with Visual Impairments: A Report on Seeking and Finding Employment. (January 2018) - Antonelli, Karla; Steverson, Anne; O'Mally, Jamie
Introduction: Career mentoring can help college graduates with legal blindness to address employment barriers. Data on specific employment outcomes and job search experiences for this population can inform job-seeking strategies for students, mentors, and service providers. Methods: A longitudinal study evaluated job-seeking activities and employment outcomes for college students with legal blindness, half of whom were randomly assigned to work with a career mentor who was also legally blind and working in the same field. Students reported job search activities and experiences, and those employed reported job details including position, compensation, and satisfaction. Results: Students spent a considerable amount of time job seeking, and reported low interviews-to-applications ratios. Trends indicated that students with mentors spent less time and effort in their job searches. Students identified challenges including job market competition, employer bias, and transportation issues. Students who found employment worked in varied fields, often in professional or skilled positions with competitive salaries. Discussion: College students with legal blindness can achieve successful employment in competitive positions, but they may require an effortful job search to address well-known employment barriers for this population. Experienced mentors may provide guidance for a more focused and efficient job search. Implications for practitioners: Invested time and effort are aspects of job seeking that students can control. Mentors can assist college students with legal blindness on those aspects, freeing time and resources to deal with systemic challenges such as employer attitudes and competition.